Curcumin protects islet cells from glucolipotoxicity by inhibiting oxidative stress and NADPH oxidase activity both in vitro and in vivo. Issue 6 (2nd November 2019) - Li, Jing; Wu, Ninghua; Chen, Xiao; Chen, Hongguang; Yang, Xiaosong; Liu, Chao
ABSTRACT: Curcumin possesses medicinal properties that are beneficial in various diseases, such as heart disease, cancer, and type 2 diabetes mellitus (T2 DM). It has been proposed that pancreatic beta cell dysfunction in T2 DM is promoted by oxidative stress caused by NADPH oxidase over-activity. The aim of the present study was to evaluate the efficacy of curcumin as a protective agent against high glucose/palmitate (HP)-induced islet cell damage and in streptozotocin (STZ)-induced DM rats. INS-1 cells were exposed to HP with or without curcumin. Cell proliferation, islet cell morphological changes, reactive oxygen species production, superoxide dismutase and catalase activity, insulin levels, NADPH oxidase subunit expression, and the expression of apoptotic factors by INS-1 cells were observed. Our results show that curcumin can effectively inhibit the impairment of cell proliferation and activated oxidative stress, increase insulin levels, and reduce the high expression of NADPH oxidase subunits and apoptotic factors induced by HP in INS-1 cells. The STZ-induced DM rat model was also used to determine whether curcumin can protect islets in vivo . Our results show that curcumin significantly reduced pathological damage and increased insulin levels of islets in STZ-induced DM rats. Curcumin also successfully inhibited the high expression of NADPH oxidase subunits and apoptotic factors in STZ-induced DM rats. These results suggest that curcumin is able to attenuate HP-induced oxidative stress in islet cells and protect these cells from apoptosis by modulating the NADPH pathway. In view of its efficiency, curcumin has potential for translation applications in protecting islets from glucolipotoxicity.